Gingival crevicular fluid from pregnant women impairs trophoblast cell function and trophoblast‐neutrophil interaction. (12th May 2022) - Hauk, Vanesa; D'Eramo, Luciana; Calo, Guillermina; Merech, Fátima; Doga, Luciana; Lara, Brenda; Gliosca, Laura; Massone, Carla; Molgatini, Susana; Ramhorst, Rosanna; Squassi, Aldo; Pérez Leirós, Claudia
Abstract: Problem: A strong association between periodontitis and higher susceptibility to pregnancy complications like preeclampsia has been reported although the mechanisms remain elusive. Trophoblast cells modulate the recruitment and functional shaping of maternal leukocytes at early stages to sustain an antiinflammatory microenvironment and fetal growth. Neutrophil activation with reactive oxygen species (ROS) release is associated with preeclampsia. Our aim was to study the effect of the gingival crevicular fluid (GCF) from pregnant women on trophoblast cell function and trophoblast‐neutrophil interaction. Method of study: Pregnant women at 16–20 weeks of gestation ( n  = 27) and non‐pregnant women ( n  = 8) as the control group were studied for gingivoperiodontal clinical score evaluation and GCF collection. Total bacteria and common periodontal pathogens were analyzed in GCF samples. The effect of each GCF sample was tested on first trimester trophoblast‐derived cells to assess cell migration, cytokine expression and glucose uptake. Also, the effect of GCF on human peripheral neutrophil chemoattraction by trophoblast cells and ROS formation was assessed. Results: Gingival crevicular fluid from pregnant women reduced trophoblast cell migration, increased proinflammatory marker expression and glucose uptake. A significant correlation between gingivoperiodontal score and trophoblast dysfunction was observed. Upon conditioning of trophoblast cells with GCF, only the GCF from pregnant women stimulated neutrophil chemoattraction. Similarly, GCF from pregnant but not from non‐pregnant controls stimulated ROS formation in neutrophils. Conclusions: Gingival crevicular fluid from pregnant women is deleterious for first trimester trophoblast cell function. These effects could lead to placental homeostasis disruption underlying a pathogenic mechanism of pregnancy complications associated to periodontal disease.